A unified metric for costing tailings dams and the consequences for tailings management. (September 2022) - Cox, Benjamin; Innis, Sally; Mortaza, Adnan; Kunz, Nadja C.; Steen, John
Abstract: Early-stage decision making on tailings disposal technology has significant and long-lasting impacts on mine economics and risk. The assumed favorable economics of slurried tailings disposal has had wide-reaching implications on the uptake of dewatered tailings technology such as paste thickeners, dry-stack and cyclone tails. This paper addresses the need for a comparable metric across tailings disposal options by the development of a financial model and unified costing metric which can be used during a mine's initial design choice and decision-making stages. The financial model developed estimates the actual cost of tailings dams in USD per dry metric tonne working within the framework of Canadian disclosure requirements. The method's utility is illustrated by applying the model to a case study of a Chilean copper mine. This case study demonstrates the usefulness of a unified metric for application in mine development proposals to improve the financial reporting transparency of TSFs. A unified cost metric would result in companies assessing their financial obligations more systematically, thereby promoting decision-making around alternatives to tailings dams in the longer term. Highlights: The actual cost of tailings storage facilities (TSFs) is undervalued in most preliminary economic assessments. Current financial reporting allows for the underestimation of the value of dewatered tailings disposal options. A unified costing metric is created as an early-stage benchmark for tailings disposal decision-making. This financial model and metric promotes improved decision-making on equipment choices.